2022
DOI: 10.1073/pnas.2214331119
|View full text |Cite
|
Sign up to set email alerts
|

Human T cells recognize HLA-DP–bound peptides in two orientations

Abstract: Human leukocyte antigen (HLA) molecules present small peptide antigens to T cells, thereby allowing them to recognize pathogen-infected and cancer cells. A central dogma over the last 50+ y is that peptide binding to HLA molecules is mediated by the docking of side chains of particular amino acids in the peptide into pockets in the HLA molecules in a conserved N- to C-terminal orientation. Whether peptides can be presented in a reversed C- to N-terminal orientation remains unclear. Here, we performed large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(42 reference statements)
2
12
0
Order By: Relevance
“…This suggests that the HLA-DP α chain, although bearing a limited specificity-determining role (see later), is the major determinant for the acceptance of the inverted peptide binding mode. These observations are in alignment with recent studies ( 28 , 33 ), which have shown that widespread inversion of peptide binders is only observed for DP and only for DP molecules with certain α chains (namely, DPA1*02:01 and DPA1*02:02). Although molecules with DPB1*03:01 have not been observed in previous studies to have inverted binders ( 32 ), our method predicts a sizable percentage (~8.1%, 83 of 1029 peptides) of inversions for DPA1*02:01-DPB1*03:01.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This suggests that the HLA-DP α chain, although bearing a limited specificity-determining role (see later), is the major determinant for the acceptance of the inverted peptide binding mode. These observations are in alignment with recent studies ( 28 , 33 ), which have shown that widespread inversion of peptide binders is only observed for DP and only for DP molecules with certain α chains (namely, DPA1*02:01 and DPA1*02:02). Although molecules with DPB1*03:01 have not been observed in previous studies to have inverted binders ( 32 ), our method predicts a sizable percentage (~8.1%, 83 of 1029 peptides) of inversions for DPA1*02:01-DPB1*03:01.…”
Section: Resultssupporting
confidence: 92%
“…On the basis of this, they hypothesized that for this molecule, peptides can bind both in a canonical (N- to C-terminal) and inverted (C- to N-terminal) orientation. This inverted binding mode was later confirmed experimentally in independent studies ( 28 , 33 ). In the context of T cell epitope prediction, Racle et al.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations